2010
DOI: 10.1039/b920143b
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relationships in metallosurfactants

Abstract: The morphology of micelles formed by three sub-classes of metallosurfactants-those with macrocyclic, linear and gemini head groups-has been studied by small-angle neutron scattering (SANS) for a series of metal-and counter-ions. All the data may be described by a model that invokes a globular micelle morphology in which the dimensions of the micelle are consistent with the known chemical structure of the constituent groups within the metallosurfactant. For two macrocyclic head group metallosurfactants, viz. 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The neutron scattering data from the surfactant-only system (h-surfactant in D 2 O) were fitted using the FISH data analysis program. 13 The data were best described by a core-shell model in which the core radius was constrained to the all trans-equivalent hydrocarbon chain length (R core ¼ 15 Å ) yielding a shell thickness (d) of 10 Å and an ellipticity (X) of 2, in good agreement with previous data, [9][10][11] see Table 1.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The neutron scattering data from the surfactant-only system (h-surfactant in D 2 O) were fitted using the FISH data analysis program. 13 The data were best described by a core-shell model in which the core radius was constrained to the all trans-equivalent hydrocarbon chain length (R core ¼ 15 Å ) yielding a shell thickness (d) of 10 Å and an ellipticity (X) of 2, in good agreement with previous data, [9][10][11] see Table 1.…”
Section: Resultsmentioning
confidence: 93%
“…For example, NiCl 2 and CuSO 4 led to significant amounts of insoluble material that could not be dissolved with reasonable variations in pH, temperature or ionic strength. However, Cu(NO 3 ) 2 and Zn(NO 3 ) 2 produced stable, clear micellar solutions (critical micelle concentrations, CMC ¼ 2-3 mM [9][10][11] ) with no solid precipitate, and these were selected for further study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the S(Q) term is essential to fit the data, previous work 22 has demonstrated that the fitting process can be insensitive to the individual parameters in the Hayter-Penfold S(Q) structure factor used for micelle-micelle charge repulsions 23 Due to the presence of a metal ion in the headgroup, there is a possibility to use small-angle X-ray scattering (SAXS) to investigate the location of the surfactant headgroups in a micelle, or to identify the surfactant shell around a microemulsion droplet. We have used this approach previously in both types of system, 1,19 but SAXS measurements cannot provide the level of detail required to determine contributions of different components to microemulsion structure. To do this a multiple contrast small-angle neutron scattering (SANS) experiment is required, using selective deuteration to highlight individual components.…”
Section: Small-angle Neutron Scattering (Sans)mentioning
confidence: 99%
“…Metallosurfactants may be defined as containing a polar transition metal ligand complex in conjunction with a hydrophobic moiety 1,2 , forming a construct in which the physical behaviour of conventional surfactants is combined with the properties of the bound transition metal ion, such as redox 3,4,5 , catalytic 6,7 , photophysical 8,9 and paramagnetic 10,11 properties. This has led to their uses in imaging 12 , DNA binding 13 The classical adsorption and self assembly behaviour of metallosurfactants observed in aqueous solution 14,15,16 affords a high local concentration of the reactive metal species and allows one to constrain a particular characteristic of the metal at an interface in a compartmentalised system, such as a microemulsion.…”
Section: Introductionmentioning
confidence: 99%